Dewatering system of a deep of excavation in urban area – Bucharest case study. (2017) - Calin, Nicoleta; Radu, Cristian; Bica, Ioan
Abstract: Many excavations for basement construction will encounter groundwater. If not suitably managed and controlled, groundwater can cause problems for excavation and the buried structures themselves. These problems can range from nuisance seepages that reduce the efficiency of construction operations, through to major inflows that can result in instability, flooding and even collapse of the excavation. Groundwater can be a significant problem when excavating for basement construction. However, with good planning and the use of suitable methods groundwater need not be a major obstacle. If an excavation is made without suitable groundwater control various problems can result: ▪ the excavation may flood as a result of groundwater inflows from water-bearing layers of soil or rocks. ▪ high pore water pressures in batter slopes at the sides of the excavation may lead to instability or seepage erosion. ▪ groundwater uplift pressures beneath the floor of an excavation can give the risk of a base heave or piping failure in the base of the excavation. ▪ groundwater pressures can cause excessive hydrostatic loads on excavation retaining structures such as concrete pile walls. Dewatering methods (also known as groundwater control methods) can be used to control groundwater and avoid these problems. This is an especial problem when excavating in water-bearing soil (such as sands and gravels) or fissured rock (such as chalk or sandstone). Without suitable control measures, inflows of groundwater can flood excavations or tunnels, and can also lead to instability when the soils or rock around the excavation weaken and collapse – either locally or on a large scale. The current modern techniques allow the execution of the deep excavations in the urban zones in more difficult geotechnical and hydrogeological conditions. The main methods which provide the removal of the groundwater from the deep excavations are: ○ Direct dewatering – the direct pumping of the water which penetrates through the walls and the background of the excavation; ○ Indirect dewatering – the general descent of the groundwater level, through point wells needle filtres or dewatering wells, done before the excavation; ○ Achieving of the watertight barrier that prevent the groundwater penetration in excavation. For the execution dry environment works, in most of the situations it is needed the lowering of the groundwater level. Dewatering works provide the possibility of dry digging execution under the groundwater level.